Akuntabilitas Dana Kelurahan terhadap Peningkatan Pembangunan melalui Permendagri Nomor 130 Tahun 2018 pada Kelurahan Ampel Kota Surabaya - Ayu Asari; IBK Bayangkara (Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the accountability of village fund management in supporting local development in Ampel Village, Surabaya City, in accordance with Ministry of Home Affairs Regulation Number 130 of 2018. Using a qualitative descriptive approach, the research examines accountability across key stages of fund management, including planning, implementation, administration, reporting, and evaluation. Data were collected through in-depth interviews, direct observation, focus group discussions, and document analysis involving village officials and community representatives. The findings indicate that accountability at the planning stage has been implemented through participatory mechanisms, although community involvement has not been fully optimized. The implementation and administrative stages demonstrate compliance with technical guidelines and financial procedures, supported by adequate documentation and internal control. Reporting and evaluation processes are conducted in a timely and transparent manner, enabling public oversight and institutional learning. Overall, the accountability of village fund management has contributed positively to improving the quality of development outcomes and strengthening public trust. However, enhancing participatory planning and systematic evaluation remains essential to ensure sustainable and inclusive local development.